Emotion Expression in Modern Literary Appreciation: An Emotion-Based Analysis - Li, Jingxia (Frontiers in Psychology, 2022)
Background: Modern literary appreciation seems to be reading literary works phenomenally. In fact, appreciation is not a general reading, which has an important difference from general reading. It is the identification and appreciation of literary works and a complex spiritual activity for people to feel, understand and imagine literary and artistic works. At the same time, literary appreciation is also a cognitive activity, an aesthetic activity, and a re-creation activity. Method: In this paper, the machine learning algorithm is creatively used to classify the emotions of figures in modern literary works, so as to analyze the emotions of the figures that the writer wanted to depict in modern literary works. Results: Experimental results verify the accuracy of the emotion classification method through experiments, which is helpful for us to better understand the emotion expression in modern literary works.